Current and emerging approaches for eliminating Borrelia burgdorferi and alleviating persistent Lyme disease symptoms - Zafar, Kashaf; Azuama, Onyedikachi C.; Parveen, Nikhat (Frontiers in Microbiology, 2024)
Lyme disease is the most prevalent tick-borne infection caused by Borrelia burgdorferi bacteria in North America. Other Borrelia species are predominately the cause of this disease in Eurasia with some distinct and various overlapping manifestations. Consequently, caution must be exercised when comparing the disease and its manifestations and treatment regimens in North America and Europe. Diagnosis of the early Lyme disease remains difficult using the currently FDA approved serological tests in the absence of a reported tick bite or of erythema migrans in many individuals, non-specific initial symptoms, and the absence of detectable anti-Borrelia antibodies in the prepatent period of infection. Furthermore, it is difficult to distinguish persistence of infection and disease versus reinfection in the endemic regions of Lyme disease by serological assays. If early infection remains untreated, spirochetes can disseminate and could affect various organs in the body with a variety of disease manifestations including arthralgias and musculoskeletal pain, neurologic symptoms and anomalies, and acrodermatitis chronicum atrophicans (ACA) in Europe. Although most patients recover after antibiotic treatment, an estimated ~10-20% patients in the United States show persistence of symptoms known as post-treatment Lyme disease syndrome (PTLDS). The causes and biomarkers of PTLDS are not well-defined; however, several contributing factors with inconsistent degree of supporting evidence have been suggested. These include antigenic debris, dysregulation of immunological response, bacterial persisters, or combination of these features. This review highlights currently employed treatment approaches describing different antimicrobials used, and vaccine candidates tried to prevent B. burgdorferi infection.